Working in Creative Partnership with Students to Co‐Produce Neuroanatomy e‐Learning Resources in a New Era of Blended Learning. Issue 4 (4th June 2021) - Border, Scott; Woodward, Charlotte; Kurn, Octavia; Birchall, Cara; Laurayne, Hailey; Anbu, Deepika; Taylor, Charlie; Hall, Samuel
Abstract : Anatomists are well placed to tackle the transition from face‐to‐face to blended learning approaches as a result of the rapidly forced changes brought about by Covid‐19. The subject is extremely visual and has, therefore, previously been a target for the development of technology‐enhanced learning initiatives over the last ten years. Today's students have come to expect the integration of technology in the classroom and remotely. They adjust quickly to the innovative use of new applications and software and have begun to integrate it within their own workflow for note taking and study aids. Given the intense drive toward blended deliveries of anatomy as a result of the Covid‐19 pandemic, it is easy to picture how the benefits of working in partnership with students (in order to achieve many of these aims) would be possible, particularly in difficult subjects like neuroanatomy. In doing so, it provides anatomists with new opportunities to engage students in a way that aligns well with best practice frameworks for engaging students through partnership. The current United Kingdom guidelines set out by Advance HE (a professional membership organization for promoting excellence in higher education) strongly encourages the higher education community to seek out appropriate academic contexts where a balance of power can be struck between staff and student to create a community of practice. If such an approach can be fully embraced by anatomists, a strong argument can be made for seizing the opportunity to optimize the benefits of student partnership work in this discipline.